Review of Fiqh Muamalah on Online Buying and Selling Practices in the Digital Era - R. Nia Marotina; Izzul Haq, Muhammad (Velocity: Journal of Sharia Finance and Banking, 2025)
This study examines online shopping practices from the perspective of fiqh muamalah, particularly in response to problems such as fraud, damaged goods, and delivery issues. Using library research methods, the study concludes that online transactions are permissible as long as they comply with Islamic principles, including mutual consent, clarity of contract terms, and the presence of fair legal oversight. The results obtained from this study indicate that online shopping is allowed, if it is in accordance with the provisions of fiqh muamalah, namely not violating the provisions of religious law, there is an agreement between the seller and the buyer if something unwanted happens between the agreement (Alimdha') or cancellation (Fasakh), and there are strict and clear supervision, sanctions, and legal rules from the government to ensure that buying and selling using online transactions is permissible for the public